Meningkatkan Kemampuan Sikap Empati Anak Usia Dini Melalui Mendongeng Cerita Sejarah Islam - Erna Budiarti; Diana Earlyana Lesmana; Nor Annisa; Hataul Santy; Reni Rulita (Journal Analytica Islamica, 2022)
The ability to empathize is included in the scope of social and emotional development of children from an early age. Empathy is part of prosocial skills which is also part of freedom of conscience. The storytelling method is an appropriate method for developing character education in early childhood because through fairy tales it will attract children's attention to remember and understand the moral values and positive character that children need to have and develop in social life so that later children can adapt socially and acceptable in social interaction in society. The purpose of this study was to obtain an overview of increasing children's empathy skills through the application of the storytelling method. This research uses a type of qualitative research using the research method of literature review or literature study which contains theories that are relevant to the problems in the research taken by the researcher. The results of the study show that storytelling of Islamic history can increase empathy in early childhood. So it can be concluded that storytelling is an effective learning method in cultivating positive moral attitudes through messages conveyed by storytellers in accordance with Islamic teachings contained in the story.